Kształtowanie umiejętności wnioskowania sylogistycznego - Smolak, Maciej (Filozofia Publiczna i Edukacja Demokratyczna, 2015)
The article consists of two parts. In the first part the author presents the characteristics of syllogistic reasoning, in the second part describes a set of exercises that are useful in teaching and developing the skill of syllogistic reasoning. The exercises belong to the teaching tools called interactive teaching methods and are of varying level of difficulty.